Comparison of polychlorinated biphenyl (PCB) induced effects on innate immune functions in harbour and grey seals - Hammond, J A; Hall, A J; Dyrynda, E A (Aquatic Toxicology, 2005)
Polychlorinated biphenyls (PCBs) are known to have detrimental effects on the innate immune system of several mammalian species. Top predators such as marine mammals may be badly affected as PCBs can bioaccumulate in their blubber to high concentrations and previous studies have suggested that harbour seals may be particularly vulnerable to the immunotoxic effects of such contaminants. To investigate the effects of PCBs on innate immune functions in phocid seals, blood samples were collected from harbour and grey seals and exposed in vitro to a mixture of Aroclors. Separated mononuclear (PBMCs) and polymorphonuclear (PMNCs) leukocytes from each species were incubated with Aroclors (at 3 and 30 ng ml(-1)) for 3 and 24 h incubation periods, after which phagocytosis, respiratory burst and cytotoxic activity were measured. The phagocytic activity of harbour seal PMNCs was decreased at both incubation times and at both Aroclor concentrations tested, but there was no effect on the grey seals. Similarly, the respiratory burst activity of harbour seals was decreased at both incubation times, but only at the higher concentration used. There were no differences in the cytotoxic activity of the PBMCs with respect to incubation times or concentrations in either species. However, differences were observed in the level of cytotoxic activity against YAC-1 target cells, with the grey seal PBMCs showing higher levels of activity. The observed differences in phagocytosis, respiratory burst and cytotoxic activity of the leukocytes following incubation with PCBs may have implications for the previously recorded differences in disease susceptibility between grey and harbour seals. (C) 2005 Elsevier B.V. All rights reserved.